A Model of Technology Acceptance and Usage: Case of Ribbon Embroidery SMEs in Indonesia - Rosyati Rosyati; Dyah N.A. Janie; Dwi W.P.S. Nugroho (Proceeding Of The International Seminar and Conference on Global Issues, 2016)
With the problem of the management and accounting information systems, this study is intended to test the model the use of technology/information systems in Ribbon Embroidery SMEs in Semarang. Several previous studies have been done using a model of the use of technology/information systems, but only partial and not comprehensive. SMEs are in need of a lot of help. This study was able to collect data obtained from 49 respondents are owners, managers and employees of the accounting department or technology/information systems. The results of this study have not been able to prove the effect of performance expectations, business expectations, social factors, facilitating conditions on the behavioral intentions in using technology/information systems. In addition, this research has not succeeded in proving that age moderates the influence of social factors and facilitating conditions on behavioral intentions and the usage of technology/information systems. Experience also has not been proven moderating influence of the business expectations on behavioral intentions. However, self-efficacy and facilitating conditions to significantly affect the behavioral intentions and the usage of technology/information systems. The gender variable was proven to have moderating effect on the influence of performance expectations on behavioral intentions. Experience was proven to have moderating effects on the influence of facilitation conditions on the use of technology/information systems. Keywords: behavioral intentions, usage, information technology, accounting information system.